Mechanism-based modular psychotherapy versus cognitive behavioural therapy for adolescents and young adults with childhood trauma experiences: study protocol for a feasibility trial within the German Center for Mental Health : protocol - Seitz, Katja I.; Schouler, Niklas; Hundertmark, Jan; Wilhelm, Maximilian; Franz, Svea; Bauer, Stephanie; Taubner, Svenja; Korn, Christoph W.; Haun, Markus W.; Ditzen, Beate; Zimmermann, Hanna; Enning, Frank; et al. (BMJ open, 2025)
Introduction Patients with mental disorders and a history of childhood trauma show an early onset of psychopathology and often a poor response to standard disorder-specific treatments. They represent a patient group which requires more personalised interventions targeting the transdiagnostic mechanisms related to early trauma and its functional consequences. The mechanism-based modular psychotherapy (MeMoPsy) approach is conceptualised as an innovative framework for psychotherapy development. It comprises independent, flexibly applicable interventions from various theoretical backgrounds and evidence-based programmes within a systematic treatment algorithm, thereby tailoring module selection to the specific needs of traumatised adolescents. - Methods and analysis In a randomised controlled feasibility trial (RCT), N=80 outpatients between 15 and 25 years of age diagnosed with various mental disorders will receive 28 individual sessions with MeMoPsy or standard cognitive behavioural therapy. MeMoPsy includes a basic module that addresses trauma history and three additional modules focusing on functional impairments known to be associated with childhood trauma: rejection sensitivity, emotion regulation and relationship difficulties. These modules are selected based on a self-report algorithm. Techniques from mentalisation-based therapy, cognitive behavioural analysis system of psychotherapy, dialectical behaviour therapy and systemic therapy are integrated in this personalised modular procedure. This proof-of-concept study aims to provide initial evidence for acceptability, feasibility and changes in self-rated and diagnostician-rated psychopathology (post-treatment and 3 months follow-up) of MeMoPsy and elucidate the mechanisms of change using psychotherapy process research, Ecological Momentary Assessment and functional magnetic resonance imaging (fMRI). - Ethics and dissemination This RCT obtained approval from independent ethics committees of participating centres and is accompanied by a data and safety monitoring board. Findings will be communicated within the research community as well as with patients and the public by the dissemination strategies of the German Center for Mental Health. - Trial registration number German Clinical Trials Register DRKS00034058.
Gesehen am 30.06.2025